Padua Days on Muscle and Mobility Medicine, March 25-29, 2025, Hotel Petrarca, Euganean Thermae, Italy: Program and Abstracts - Barbara Ravara; Paolo Gargiulo; David Hood; Lars Larsson; Christiaan Leeuwenburgh; Maria Chiara Maccarone; Stefano Masiero; Philippe Perrin; Amber Pond; Riccardo Rosati; Piera Smeriglio; Lee Sweeney; et al. (European Journal of Translational Myology)
Medium-sized scientific conferences held in hotels large enough to accommodate all participants increase opportunities for constructive discussion during breaks, and for evenings that bring together young and senior experts of basic sciences and clinical specialties. Time for group discussions offer opportunities for new collaborations and for jobs for young researchers. Since 1991 the Padova Muscle Days have offered collaborative opportunities that have matured into innovative multidisciplinary results to the point that it came naturally for us to underline it with a neologism now included in the title of the 2025 event: "Mobility Medicine". It is a discipline which developed naturally when we brought together fragmented areas of knowledge into one meeting. The Padua Days on Muscle and Mobility Medicine 2025 (2025Pdm3) will be hosted at the Hotel Petrarca, Euganean Thermae (Padua, Italy) from 25 to 29 March 2025. The list of unique sessions within the included program and the following Collection of Abstracts testify that it is possible to organize valid countermeasures to the inevitable tendencies towards hyper-specialization that the explosive increase in scientific progress brings. The European Journal of Translational Myology and Mobility Medicine (Ejtm3) will accept typescripts on results presented at the 2025Pdm3. Furthermore, an additional option for publication of full original Articles or Reviews is the Special "New Trends in Musculoskeletal Imaging" of the MDPI Journal Diagnostics, because diagnosis is essential to manage and follow-up neuro- metabolic- muscular- disorder and the decay of performances in aging. We hope that many will share our dreams and we make them come true at the 2025 Pdm3 Conference.